FOOD PRODUCT CONTAMINATION RISKS AT DIFFERENT STAGES OF PRODUCTION - O. I. Lavrukhina; V. G. Amelin; L. B. Prokhvatilova; O. I. Ruchnova (Ветеринария сегодня)
The review presents analysis of possible contaminations of food products at different production stages. It was demonstrated that to perform scientifically based assessment of food product contamination it is necessary not only to test for safety criteria stipulated in the regulatory framework where special attention is given to determination and rationing of pesticides, veterinary drugs, their metabolites, natural toxins, allergens and toxic chemical elements, dioxins and polychlorinated biphenyls. It is also important to consider the specificity of environmental load in the region and critical control points of the specific product manufacturing. It especially concerns the raw material processing stage which poses additional risk of contamination of the finished product both with technologically justified additives (during their uncontrolled use) as well as banned additives (e.g. melanin, used in melamine-formaldehyde resin production for plastic manufacturing, as colorant and fertilizer) as well as degradation products (nitrosamine, acrylamide, chlorpropanol appearing as a result of heat treatment). It should be noted that some chemical contaminants like chemical elements (plumbum, mercury, cadmium, arsenic) can get into food products at different stages of their production. This fact shall be taken into account during their content assessment. Feed can be a potential source of contamination of raw materials and animal food products as a result of bioaccumulation and transfer of toxic agents and their metabolites to meat, offal, milk and eggs. Total risk for humans will be determined basing not only on consumption of plant products containing toxins, but also on secondary contaminants (toxins and their metabolites) getting in to the body with food products and animal raw materials.